UJI ANTIOKSIDAN EKSTRAK PIGMEN KAROTENOID DAN SITRULIN PADA KULIT BUAH BLEWAH (Cucumis melo L.) SECARA IN VITRO (METODE DPPH) - Antonius Padua Ratu; Nadia Fahmi Silabi; Padmono Citroreksoko (Jurnal Farmamedika (Pharmamedika Journal), 2016)
Antioxidants stabilize free radicals with a complete the lack of electrons from free radicals and inhibiting the chain reaction of free radical formation. The purpose this research is to determine the amount of the antioxidant potential of the cantaloupe skin extracts and the effect of different test result of pigment carotene and citrulline in skin cantaloupe extracts to the extraction stage. Cantaloupe skin with drying and without drying treatment is gradually extracted using three solvents (petroleum ether-acetone-water). The highest antioxidant activity shown by extracts water without drying treatment (667.30 mg / L), which was significantly different (P <0.05) with acetone and petroleum ether (996.65 and 2368.26 mg / L). Treatment with drying only on petroleum ether extract (1607.28 mg / L), which provides activity compared with acetone and water (2871.54 and 2290.75 mg / L). However, cantaloupe skin extract antioxidant activity was lower compared with β-carotene and vitamin C. Treatment without drying also give the highest pigments carotenoid shown by extracts aceton (β-caroten 11,32 mg/L, lycopene 0,29 mg/100g) and level of citrulline in water extracts (29,91 mg/L). The difference of effect in simplisia treatment and solvent on the activity of antioxidants and pigments carotenoid levels were significantly different (P <0.05), whereas the levels of citrulline in the simplisia treatment was not significantly different for solvent acetone and significantly different (P <0.05) for solvent petroleum ether and water.